BUILDING ELEMENTARY STUDENTS' MOTIVATION THROUGH SOCIO-EMOTIONAL COMPETENCE IN DIFFERENTIATED LEARNING - Prajayana, Marfita Ike; Yayuk, Erna; Kuncahyono, Kuncahyono (Universitas Labuhanbatu, 2025)
Purpose – Education plays a crucial role in shaping high-quality human resources, with curriculum adaptation being essential to meet the demands of an ever-changing world. One key element is differentiated instruction, which accommodates diverse student learning needs through differentiation in content, process, and product. However, its implementation faces challenges, particularly in integrating differentiated instruction with the development of students' social-emotional competencies. This study aims to evaluate the effectiveness of integrating differentiated instruction with social-emotional competencies in enhancing students' learning motivation.Methodology – This study was conducted at SDN 5 Sumber using a qualitative descriptive approach through classroom observations, interviews, and document analysis. The participants included the principal, teachers, and fourth-grade students. Data were analyzed using Miles and Huberman’s interactive model: data collection, data reduction, data presentation, and conclusion drawing.Findings – The study found that differentiation was more frequently applied to the learning process rather than content and product. Teachers utilized auditory, visual, and kinesthetic strategies, but content differentiation was limited. Social-emotional competencies were developed through group discussions, reflective sessions, and collaborative activities, leading to increased student engagement, independence, and emotional regulation. Evaluations used formative and summative assessments, with observation rubrics for assessing social-emotional competencies.Contribution – This study contributes to the understanding that integrating differentiated instruction with social-emotional competency development can effectively enhance students' learning motivation. It also highlights the need for improved teacher training and resources to support content and product differentiation.